Arduino Uno-Based Fire Alarm System - Nur Asmi Rahmawati; Hermansyah, Hermansyah (Jurnal Sains dan Teknik Terapan, 2024)
Fire is a disaster that can cause significant losses to life and property. Therefore, the development of an effective fire alarm system is essential in order to protect safety and security. This research aims to develop an "Arduino Uno-Based Fire Alarm System" that uses Arduino Uno as the main control platform. This system is designed to detect abnormal temperature increases and the presence of smoke associated with a fire. The research methodology includes needs analysis, system design and planning, prototype development, testing, and evaluation. Temperature and smoke sensors are used to detect temperature changes and the presence of smoke. Arduino Uno is utilized as a controller to integrate the sensors and alarm system, providing early warnings through sound. The testing results of the device shows excellent responsiveness. The response time from detecting high-temperature situations to activating the alarm is recorded in seconds, enabling quick action to address emergencies